2005
DOI: 10.1603/0022-0493-98.3.732
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Substerilizing Doses of Gamma Radiation on Adult Longevity and Level of Inherited Sterility in <I>Teia anartoides</I> (Lepidoptera: Lymantriidae)

Abstract: The effects of substerilizing doses of gamma radiation on the longevity and level of inherited sterility in the Australian moth Teia anartoides Walker were determined. Six day-old male pupae were treated with 0, 100, and 160 Gy of gamma radiation by using a 1.25 MeV Cobalt60 irradiation source. Laboratory studies of male longevity showed that radiation had little impact in adult moths of the P1, F1, and F2 generations. Inherited deleterious effects resulting from irradiation were observed in the progeny of F1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 20 publications
1
25
0
Order By: Relevance
“…In practice, the success of IL × IL matings are seldom measured, due to difficulties in producing enough offspring in the laboratory to make a robust estimate. ILincompatibility is usually assumed, perhaps because of the relatively low survival rate of IL females in many species ( Carpenter et al , 2005 ), although, conversely, the fertility of the irradiated line has been shown to recover in subsequent generations in some species ( Graham et al , 1972;Zhang et al , 1993;Arthur et al , 2002;Wee et al , 2005 ). Other aspects of IL fitness, such as survivorship and competitiveness are rarely measured, but sensitivity analysis suggests that IL competitiveness at least is less likely to have a major influence on the outcome of SIT programmes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In practice, the success of IL × IL matings are seldom measured, due to difficulties in producing enough offspring in the laboratory to make a robust estimate. ILincompatibility is usually assumed, perhaps because of the relatively low survival rate of IL females in many species ( Carpenter et al , 2005 ), although, conversely, the fertility of the irradiated line has been shown to recover in subsequent generations in some species ( Graham et al , 1972;Zhang et al , 1993;Arthur et al , 2002;Wee et al , 2005 ). Other aspects of IL fitness, such as survivorship and competitiveness are rarely measured, but sensitivity analysis suggests that IL competitiveness at least is less likely to have a major influence on the outcome of SIT programmes.…”
Section: Discussionmentioning
confidence: 99%
“…Knipling (1970) points out that the use of population models to guide inherited sterility SIT relies on a very good understanding of the biology of the system under consideration. Today, the biological mechanisms underlying inherited sterility in Lepidoptera are well understood ( Carpenter et al , 2005 ), and crossing experiments and fitness measurements have become a routine element of any SIT programme ( Bloem et al , 1999a , b;Suckling et al , 2004;Wee et al , 2005 ). We believe that this is an opportune time for new population models to inform inherited sterility SIT programmes, particularly models that incorporate further biological realism such as demographic stochasticity, Allee effects and spatial structure, all of which are known to have major influences on the viability and dynamics of small populations.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Sitotroga cerealella (Olivier) Angoumois grain moth Cogburn et al 1966 Lymantriidae Lymantria dispar (L.) gypsy moth Mastro et al 1989Proshold et al 1993Proshold 1995Maksimovic 1972Mastro et al 1989Mastro 1993Strom et al 1996 Teia anartoides Walker painted apple moth Suckling et al 2002Wee et al 2005Suckling et al 2002 Helicoverpa zea (Boddie) corn earworm bollworm tomato fruitworm Carpenter et al 1987cCarpenter and Gross 1989Carpenter 1991Carpenter and Wiseman 1992aHamm and Carpenter 1997North and Snow 1978Carpenter et al 1987a, 1987b, 1989Carpenter and Gross 1993Mannion et al 1994 Heliothis virescens (F.) tobacco budworm Proshold and Bartell 1970, 1972a, 1972bGuerra and Garcia 1976North and Snow 1978 Spodoptera exigua (Hübner) beet armyworm Debolt 1973Carpenter et al 1996 Spodoptera frugiperda (J. E. Smith) fall armyworm Carpenter et al 1983, 1986, 1997Carpenter and Young 1991Arthur et al 1993Hamm and Carpenter 1997Carpenter et al 1985 Carpenter and Wiseman 1992b Plodia interpunctella (Hübner) Indian meal moth Cogburn et al 1966Ashrafi et al 1972Ashrafi and Roppel 1973Brower 1976,...…”
Section: Makee and Saour 1997mentioning
confidence: 99%
“…kurstaki. In February 2003, releases of partially sterile males irradiated as pupae at 100 Gy (Suckling et al 2002, Wee et al 2005 were initiated at three sites with known or suspected painted apple moth breeding populations. By May 2003, 45 000 males had been released, and recapture ratios in virgin female baited traps averaged ca.…”
Section: Painted Apple Mothmentioning
confidence: 99%